If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -16 = 92 Reorder the terms: -16 + 12x = 92 Solving -16 + 12x = 92 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 12x = 92 + 16 Combine like terms: -16 + 16 = 0 0 + 12x = 92 + 16 12x = 92 + 16 Combine like terms: 92 + 16 = 108 12x = 108 Divide each side by '12'. x = 9 Simplifying x = 9
| 5(3x+2)=70 | | -10c^3-5c^2=0 | | 8t+12p-2t-20p+7= | | 10=-x-3 | | (x+1)(x+3)=-1 | | 6x/2-(2x-3)/5=5x/3-2 | | 6a/2-(2a-3)/5=5a/3-2 | | (x+2)(x+14)=-36 | | -2-27= | | x+x-2=4 | | 356844m-1g=1g-563434646m+1 | | 2x^2-38=12 | | 5x-9=2x+66 | | 2(20a-1)/3=10a+1 | | 5x-2=q | | x^2-7x=12 | | n*6+12/.2-4.5=126 | | 3q-4=6-q | | Fx+82=12x+10 | | 233-6x=30x+21 | | 3x^2-35=2x | | 7-7x=81+21x | | Y^2-8y=-12 | | 13+5(12+y)-8=16 | | -40x-5x=10-10x | | 5(x-9)/4=4(x+9)/5 | | 57-4x=5x+18 | | 15x-12x^2-40=0 | | 61-2x=7x+21 | | -5(t-3)+7t=5t-7 | | 2x-1=6x-4 | | 4y-36=-12y |